2019
DOI: 10.1111/his.13819
|View full text |Cite
|
Sign up to set email alerts
|

The expanding morphological and genetic spectrum of MYOD1‐mutant spindle cell/sclerosing rhabdomyosarcomas: a clinicopathological and molecular comparison of mutated and non‐mutated cases

Abstract: mutated cases were reclassified as spindle embryonal (n = 3), dense embryonal (n = 1) and unclassifiable (n = 1) RMSs. Conclusion: MYOD1-mutant RMSs are uncommonly mutated with PIK3CA and behave aggressively with an expanded morphological and genetic spectrum, including lipoblastic differentiation, multinucleated cells and the alternative p.E118K mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Including our six cases, the MYOD1 p.L122R hotspot mutation has been reported in 30 pediatric patients (Table 2) [26]. Notably, tumors with the MYOD1 mutation were more likely to arise in the head or neck (40%; 12/30) and more commonly diagnosed in adolescence (63%; 19/30).…”
Section: Resultsmentioning
confidence: 86%
“…Including our six cases, the MYOD1 p.L122R hotspot mutation has been reported in 30 pediatric patients (Table 2) [26]. Notably, tumors with the MYOD1 mutation were more likely to arise in the head or neck (40%; 12/30) and more commonly diagnosed in adolescence (63%; 19/30).…”
Section: Resultsmentioning
confidence: 86%
“…While several ERMS and ARMS cell lines are available for research [39], the establishment of the first SSRMS cell line from an adolescent was only recently reported [29]. Indeed, SSRMS is a rare RMS subtype that is often characterized by aggressive progress, especially when exhibiting a MYOD1 mutation [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, desmin is frequently expressed by SSRMS and a focal positivity for myogenin (MYOG), combined with a high proliferative index (marker of proliferation Ki-67), has been reported, while the ARMS typic paired box (PAX)-forkhead box protein O1 (FOXO1) fusion proteins are absent in SSRMS [14][15][16]. Though expressing myogenic marker proteins, the completion of myogenic differentiation is inhibited in SSRMS, due to frequently observed recurrent MYOD1 mutations [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“… 7 TIAL1 protein intracellularly binds with its target mRNA, which generally decreases their stability or inhibits its translation and participates in various cellular functions. 7 - 9 …”
Section: Introductionmentioning
confidence: 99%
“… 8 MyoD1 and myogenin are myogenic regulatory protein that is expressed in the early stage of skeletal muscle differentiation, which is only expressed in embryonic skeletal muscle. 8 , 10 Zhu et al 5 reported that Long non-coding RNA MBNL1-AS1 regulates proliferation, migration, and invasion of cancer stem cells in colon cancer. The present study aimed to investigate the function and mechanism of MBNL1 in skin squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%